Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada Departemen Sewing - Halawa, Intan Trimei; Rahayu, Enik (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze the influence of work environment and work motivation on employee performance in the Sewing Department of PT. Sumbiri. The study focuses on how these two factors can improve employee productivity and effectiveness in completing tasks. The approach used refers to human resource management theory and work motivation theory. Data were collected through a survey using a closed questionnaire compiled based on a Likert scale and distributed to 240 respondents who were active employees in the Sewing Department. The analysis was carried out using a quantitative method, using multiple linear regression. The results of the study indicate that a conducive work environment reviewed from physical, social, and comfort factors, has a positive and significant effect on employee performance. Meanwhile, high work motivation, in both financial (salary, bonuses) and non-financial (recognition, career development opportunities) forms, also contributes significantly to increased productivity. These findings show that the synergy between a good work environment and optimal work motivation has a stronger effect on improving employee performance than the effect of each variable separately. This study has limitations in its scope, as it only covers one department within one company. Therefore, the generalization of the results must be done carefully. In the future, further research is recommended to cover other work units or different companies to expand the scope of the analysis.